Vegetable Rennet Tablets for Fresh Cheese Making - R F Sitepu (Jurnal Peternakan Integratif, 2020)
Indonesia has a Muslim population of around 200 million and many make religious trips to Arabia and taste fresh cheese. Therefore in Indonesia there is a demand for fresh cheese. In this regard, there is also a need to use a halal cheese starter. The purpose of this study is to prove that the use of plant-based rennet is able to produce fresh cheese which is also a halal rennet because it comes from plants. A1 = 0,1 A2 = 0,2 A3 = 0,3 and the factor B storage time (days) is B0 = 0 days, B1 = 5 B2 = 10 and B3 = 15. Variables measured include water content, dry matter, protein, fat from fresh cheese and analysis of the cost of making fresh cheese with a commercial rennet starter compared to vegetable rennet. The results showed that the dosage of using vegetable rennet papain enzyme was 0.2 g and optimum storage time for 10 days in increasing protein content and dry matter content and being able to reduce fat and water content in fresh cheese from Murrah buffalo milk.